PH and thermo dual-sensitive copolymers with fluorescent properties grafted mesoporous silica SBA-15 via metal-free ATRP. (15th March 2022) - Su, Hui-Ling; Yang, Mei-Mei; Liu, Min; Fu, Jia-Wei; Wang, Yan-Hua; Yao, Ming-Xiu; Yang, De-Hang; Wang, Li-Ping; Li, Guang
Graphical abstract: PH-sensitive DEAEMA, temperature sensitive NIPAM and Eu complex were randomly copolymerized on the SBA-15 surface. SBA-15- g -PDEAEMA- co -PNIPAM- co -Eu complex was pH and thermo dual-sensitive hybrid material with fluorescent properties, which had good dispersion under low temperature and acid condition. Highlights: SBA-15- g -PDEAEMA- co -PNIPAM- co -Eu complex was synthesized by metal free SI-ATRP. PTH was used as photocatalyst of metal free SI-ATRP. The structure and special performance of the hybrid material were investigated. The hybrid material has fluorescent properties, pH and thermo dual-sensibility. Abstract: Well-defined pH and thermo dual-sensitive random copolymers poly(2-(diethylamino)ethyl methacrylate)– co -poly(N-isopropylacrylamide)– co -Eu complex with fluorescent properties grafted mesoporous silica SBA-15 (SBA-15- g -PDEAEMA- co -PNIPAM- co -Eu complex) was prepared by surface-initiated metal-free atom transfer radical polymerization (metal-free ATRP). The ATRP initiator 2-bromoisobutyryl bromide (BIBB) was immobilized on the SBA-15 surfaces followed by metal-free ATRP of 2-(diethylamino)ethyl methacrylate) (DEAEMA), N-isopropylacrylamide (NIPAM) and Eu complex. The hybrid material was characterized by fourier transform infrared spectroscope (FT-IR), nuclear magnetic resonance (NMR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscope (TEM), atomic force microscope (AFM), thermal gravimetric analysis (TGA), N2 adsorption/desorption measurements, X-ray powder diffraction (XRD), Fluorescence spectrum and Nanoparticle Size-Zeta potential analyzer. The results showed that the SBA-15- g -PDEAEMA- co -PNIPAM- co -Eu complex hybrid material has been prepared successfully. The pore size, pore volume and specific surface area of SBA-15 decreased after grafting of the copolymers, but the ordered structure of SBA-15 pore still remained. The fluorescence testing suggested that the hybrid material had good fluorescence characteristics. The pH and temperature sensitivity analysis suggested that the hybrid material dispersion was good under low temperature and acid condition because the polymer chains stretched.